Investigations of the g factors and local structure for orthorhombic Cu²+(1) site in fresh PrBa₂Cu₃O₆+x powders - Kuang, M.Q.; Wu, S.Y.; Song, B.T.; Hu, X.F. (Condensed Matter Physics, 2012)
The electron paramagnetic resonance (EPR) g factors gx, gy and gz of the orthorhombic Cu²⁺ (1) site in fresh PrBa₂Cu₃O₆+x powders are theoretically investigated using the perturbation formulas of the g factors for a 3d⁹ ion under orthorhombically elongated octahedra. The local orthorhombic distortion around the Cu²⁺(1) site due to the Jahn-Teller effect is described by the orthorhombic field parameters from the superposition model. The [CuO6]¹⁰⁻ complex is found to experience an axial elongation of about 0.04 Å along c axis and the relative bond length variation of about 0.09 Å along a and b axes of the Jahn-Teller nature. The theoretical results of the g factors based on the above local structure are in reasonable agreement with the experimental data. g фактори gx, gy i gz електронного парамагнiтного резонансу для орторомбiчного вузла Cu²⁺(1) в чистому порошку PrBa₂Cu₃O₆+x теоретично дослiджуються, використовуючи формалiзм теорiї збурень для цих параметрiв для 3d⁹ iона в орторомбiчному видовженому октаедрii. Локальна орторомбiчна дисторцiя навколо вузла Cu²⁺(1), спричинена ефектом Яна-Теллера, описується за допомогою параметрiв ор-торомбiчного поля iз суперпозицiйної моделi. Знайдено, що комплекс [CuO6]¹⁰⁻ пiддається аксiальному видовженню близько 0.04 Å вздовж c осi i вiдносна змiна довжини зв’язку природи Яна-Теллера є приблизно 0.09 Å вздовж осей a i b. Теоретичнi результати для g факторiв, що базуються на вище згаданiй локальнiй структурi, непогано узгоджуються з експериментальними даними.